Qiliqiangxin Modulates the Gut Microbiota and NLRP3 Inflammasome to Protect Against Ventricular Remodeling in Heart Failure - Lu, Yingdong; Xiang, Mi; Xin, Laiyun; Zhang, Yang; Wang, Yuling; Shen, Zihuan; Li, Li; Cui, Xiangning (Frontiers in Pharmacology, 2022)
Aims. Pathological left ventricular (LV) remodeling induced by multiple causes often triggers fatal cardiac dysfunction, heart failure, and even cardiac death. This study aimed to investigate whether Qiliqiangxin (QL) could improve LV remodeling and protect against heart failure via modulating gut microbiota and inhibiting Nod-like receptor pyrin domain 3 (NLRP3) inflammasome activation. Methods. Rats were respectively treated with QL (100 mg/kg/day) or valsartan (1.6 mg/kg/day) by oral gavage after transverse aortic constriction or sham surgery for 13 weeks. Cardiac function and myocardial fibrosis were assessed. In addition, gut microbial composition was assessed by 16S rDNA sequencing. Furthermore, rats’ hearts were harvested for histopathological and molecular analysis including immunohistochemistry, immunofluorescence, TUNEL and western blot. Key findings. QL treatment preserved cardiac function including LV ejection fraction, fractional shortening, and markedly improved the LV remodeling. Moreover, heart failure was related to the gut microbial community reorganization like a reduction in Lactobacillus, while QL reversed it. Additionally, the protein expression levels like IL-1β, TNF-α, NF-κB and NLRP3 were decreased in the QL treatment group compared to the model one. Conclusion. QL ameliorates ventricular remodeling to some extent in rats with heart failure by modulating the gut microbiota and NLRP3 inflammasome, which indicates the potential therapeutic effects of QL on those who suffer from heart failure.